Ecotoxicity and recovery of Poecilia reticulata exposed to cosmetic effluent, graphene oxide, iron oxide nanoparticles and magnetic graphene oxide - Walter de Souza Rodrigues; João Marcos de Lima Faria; Diego Stéfani Teodoro Martinez; Theodoro da Rosa Salles; Victoria Costa da Silva; Débora dos Santos Pereira; Ryan Marques Rezende; Ana Luiza Torres Soares; Isabela Cristina Louza Goulart; Jordana Duarte de Souza; Lucas Camilo Moraes Alves; Simone Maria Teixeira de Sabóia-Morais (Aquatic Toxicology, 2026)

Metallic trace element concentrations, vertical patterns and environmental implications in soils under the “cabruca” agroforestry system of Brazil's largest cocoa-producing region - Tatiana Reis dos Santos Bastos; João Carlos Medeiros; Clistenes Williams Araújo do Nascimento; Paula Nascimento Alves; Pâmalla Graziely Carvalho Morais; Glécio Machado Siqueira; Maria Eugênia Ortiz Escobar; Kaique Mesquita Cardoso; Thomas Vincent Gloaguen; Simone Aparecida da Silva Lins; Cácio Luiz Boechat (Science of The Total Environment, 2026)

Image-based phenotyping of castor bean seeds for morphological traits, seed weight prediction, and assessment of genetic diversity - Diego Andrade Santos; Diego Fernando Marmolejo Cortes; Mylena Almeida dos Santos; Myriam El Adas; Bismarck Ferreira de Morais; Denise Barreto dos Santos; Tairone da Silva de Almeida; Christian Adalberto Santos de Queiroz; Gabriel da Paixão Fernandes; Ailan Santos de Jesus; Rafaella da Silva Rodrigues; Daniel Santos Alves; et al. (Euphytica, 2026)
Digital seed phenotyping offers an efficient and objective alternative to conventional, labor-intensive methods for morphological characterization in plant breeding programs. In castor bean, rapid and reliable tools are essential to support genetic improvement. This study evaluated the potential of digital phenotyping for seed characterization and its application in breeding. Seeds from 65 accessions (2023) and 51 accessions (2024) were photographed with an RGB camera and processed in ImageJ® for extraction of morphological traits. Agreement between digital and manual measurements was assessed by correlation and Bland–Altman analysis, while machine learning models were trained to predict hundred-seed weight (HSW). Genetic diversity was explored using principal component analysis (PCA) and clustering, and variance components and heritability were estimated with mixed linear models. Digital phenotyping showed strong agreement with manual measurements (r = 0.95–0.97) and enabled accurate HSW prediction, with Ridge Regression achieving the best performance (R 2 = 0.88; RMSE = 3.83; MAE = 3.19). PCA explained 85.7% of the variance and revealed three phenotypic clusters. Traits such as seed length (H 2 = 0.88) and aspect ratio (H 2 = 0.87) exhibited high heritability, while roundness (H 2 = 0.79), perimeter (H 2 = 0.72), and area (H 2 = 0.67) were moderate. These findings demonstrate that digital phenotyping is a reliable and high-throughput method for castor bean seed characterization, supporting genotype selection and the integration of machine learning approaches into breeding programs for greater precision and efficiency.

Assessment of some potentially toxic elements on a watershed-scale through an integrated chemical and biological monitoring framework in the Caatinga-Atlantic Forest ecotone, Northeast Brazil - Kaíque Mesquita Cardoso; Clístenes Williams Araújo do Nascimento; Douglas Gonçalves da Silva; Simone Aparecida da Silva Lins; Maria Eugenia Ortiz Escobar; Pâmalla Graziely Carvalho Morais; Tatiana Reis dos Santos Bastos; Cácio Luiz Boechat (Environmental Science and Pollution Research, 2026)
The concern for water quality is a critical issue in many countries around the world. The monitoring of water resources should be implemented to ensure water management, especially when dealing with already impacted systems. Urbanization is an impactful type of activity that contributes to the release of potentially toxic elements (PTEs) into the ecosystems. The identification of plant species with the ability to tolerate high levels of contaminants could be an alternative to remove contaminants from these environments and to evaluate the plants as bioindicators. The objective of this study was to assess the surface water and sediment quality of the Verruga River and test the aquatic macrophytes’ potential as biomonitors of some PTEs: Cd, Co, Cr, Cu, Mn, Ni, Pb, and Zn. Ten sampling points were included in the study, ranging from the source to the mouth of the river. Samples of surface water, sediments, and macrophytes were collected. In situ and laboratory analyses were performed. Direct readings of PTEs in surface water, extracts from plants and sediments were performed using ICP-OES. Quality reference guides were used. The mobility of the elements can be better visualized by the correlations between the parameters of the sediments than of the water. Concentration of Cd, Cu, Mn, Ni, Pb and Zn in surface water, sediments and aquatic plants reached different levels and some parameters exceeded guidelines on environmental quality. The species Heteranthera reniformis and Eichhornia crassipes are promising macrophytes for studies on biomonitoring of PTEs in the aquatic environment of the Verruga River. Graphic Abstract

Coarse particulate matter air pollution in Porto Metropolitan area, Portugal: time series analysis, trends and implications for public policies - Simone Georges El Khouri Miraglia; Ronan Adler Tavella; Daniela Debone; Rui Moreira Barbosa; Flavio Manoel Rodrigues da Silva Júnior; Clara Lopes Ribeiro; Simone Morais; Marisa Alexandra Marques Freitas (Environmental Science and Pollution Research, 2026)
Air pollution remains a persistent environmental and public health concern in urban regions. This study presents a 22-year analysis (2001–2022) of coarse particulate matter (PM 10 ) concentrations across 15 monitoring stations in the Porto Metropolitan Area (PMA), Portugal. The stations, pre-classified by national authorities as traffic, background-urban, background-suburban, or industrial, were used to assess long-term temporal trends and spatial variability. Annual mean PM 10 concentrations were calculated and linear regression was applied to evaluate trends. Differences between station types were tested using statistical analysis. The results revealed consistent decline in PM 10 levels from the early 2000s to the mid-2010s, followed by stagnation or increases at several stations in the final years of the series. While higher concentrations were historically observed at traffic and industrial sites, no statistically significant differences in annual mean PM 10 concentrations were found between stations of different classifications or within classifications, even when comparing distinct time periods. This homogeneity suggests widespread regional exposure, likely driven by shared emission sources, atmospheric transport, and urban development patterns across the PMA. When compared to World Health Organization (WHO) air quality guidelines, exceedances were frequent and persistent. From 2001 to 2011, nearly all stations with valid data exceeded the 2005 guideline of 20 µg/m 3 . Between 2012 and 2020, the exceedances gradually decreased, although several stations still surpassed the guideline. However, under the 2021 WHO guideline (15 µg/m 3 ), all stations with valid data for 2021 and 2022 again exceeded the guideline. These findings highlight the need for integrated, long-term air quality policies. Clinical trial number: Not applicable.

Morphological and elemental characterization of fine and ultrafine particulate matter generated from fires - Gabriel Sousa; Rui Azevedo; Agostinho Almeida; Simone Morais; Cristina Delerue-Matos; Xianyu Wang; Francisca Rodrigues; Maria Freitas; Marta Oliveira (Environmental Research, 2026)

Investigation of Phytol as an Inhibitor of the Efflux Pump (QacA/B) in Staphylococcus aureus: in silico and in vitro Studies - José Weverton Almeida-Bezerra; Carlos Alonso Leite dos Santos; Saulo Almeida Menezes; Cícera Datiane de Morais Oliveira-Tintino; Rafael Pereira da Cruz; Adrielle Rodrigues Costa; Janaína Esmeraldo Rocha; Daniel Sampaio Alves; Simone Galdino de Sousa; Ewerton Yago de Sousa Rodrigues; Gabriel Gonçalves Alencar; José Maria Barbosa Filho; et al. (Pharmaceutical Research, 2026)

Integrated in Vitro, in Vivo, Molecular Docking, and ADMET in Silico Assessment of β-Caryophyllene as a NorA Efflux Pump inhibitor in Resistant Staphylococcus Aureus (MRSA) - José Weverton Almeida-Bezerra; José Thyálisson da Costa Silva; Cícera Datiane de Morais Oliveira-Tintino; Adrielle Rodrigues Costa; Viviane Bezerra da Silva; Maria Flaviana Bezerra Morais-Braga; Irwin Rose Alencar de Menezes; Ana Carolina Ferreira Araujo; Lucas Yure Santos da Silva; Daniel Sampaio Alves; Guilherme Fernandes Teixeira; Lucas dos Santos Sa; et al. (Current Microbiology, 2026)

Micronucleus assay in buccal and urothelial epithelial cells of wildland firefighters exposed to wildfire smoke - Filipa Esteves; Joana Madureira; Bela Barros; Sara Alves; Josiana Vaz; Marta Oliveira; Klara Slezakova; Adília Fernandes; Maria do Carmo Pereira; Simone Morais; Stefano Bonassi; João Paulo Teixeira; et al. (Journal of Hazardous Materials, 2025)

Iron oxide nanoparticles (γ-Fe2O3) combined with microcystin-LR induce severe histopathological damage with potential for recovery in the intestinal tissue of Poecilia reticulata - Lucas Camilo Moraes Alves; João Marcos de Lima-Faria; Milena Lima Brito; Jascieli Carla Bortolini; Bruno Oliveira Silva Duran; Simone Maria Teixeira de Sabóia-Morais (Ecotoxicology, 2025)

Impact of wildfire emissions exposure on the associations between levels of lung injury, lipid peroxidation, DNA oxidation, and exposure biomarkers - Bela Barros; Ana Margarida Paiva; Rui Azevedo; Sara Alves; Filipa Esteves; Adília Fernandes; Josiana Vaz; Maria José Alves; Klara Slezakova; João Paulo Teixeira; Solange Costa; Agostinho Almeida; et al. (Science of The Total Environment, 2025)

Post-weaning exposure to cannabidiol disrupts testicular cytoarchitecture and sperm quality in mice - Renata K. Carvalho; Maingredy R. Souza; Akemy N. Nishimura; Edvaldo M. Silva; Cinthia R.B. Silva; Francisco S. Guimarães; Monica L. Andersen; Simone M.T. Sabóia-Morais; Renata Mazaro-Costa (Reproductive Toxicology, 2025)

Impact of occupational exposure to wildfire events on systemic inflammatory biomarkers in Portuguese wildland firefighters - Filipa Esteves; Joana Madureira; Bela Barros; Sara Alves; Joana Pires; Sandra Martins; Marta Oliveira; Josiana Vaz; Klara Slezakova; Maria do Carmo Pereira; Adília Fernandes; Simone Morais; et al. (Environmental Research, 2025)

Air Pollution and Health Impacts of Wildfire Seasons: Insights from Northern Portugal - Bela Barros; Marta Oliveira; Simone Morais (Water, Air, & Soil Pollution, 2025)
Wildfires emit significant amounts of pollutants into the atmosphere, which can cause a range of health effects, from acute symptoms to increased emergency visits, hospital admissions, and even mortality in the general population. This study aimed to characterize, for the first time, the associations between wildfire season with indicators of public human health surveillance in the Northern region of Portugal (2019–2022). Daily air pollutant data [particulate matter with aerodynamic diameter less than 10 µm (PM₁₀) and 2.5 µm (PM₂.₅), ozone (O₃), and itrogen dioxide (NO₂)], monthly emergency room visits, and regional expenses with medication dispensing were characterized and mortality impacts were estimated. Wildfire season was responsible for higher PM₁₀ and PM₂.₅ (up to + 90%), O₃ (up to + 51%), and NO₂ (up to + 39%); some days (up to 8%) surpassed limits established by national regulations and/or WHO guidelines. The total burned area correlated with monthly levels of PM₁₀, PM₂.₅, and O₃ (0.467 < r < 0.943; p ≤ 0.039). Wildfire season months presented more emergency visits to urgent care (up to + 128%; p > 0.05) and regional monthly health costs due to outpatient medication for blood volume and electrolyte imbalance (+ 12–31%; p > 0.05). During wildfire season, the number of urgent pediatric visits correlated with O₃ levels ( r = 0.606, p = 0.013). During large forest fires (> 100 hectares), a maximum of 36 and 330 estimated deaths were attributed, respectively, to short-term and long-term exposure to PM₁₀, PM₂.₅, O₃, and NO₂ above WHO guidelines. The findings highlight the need to improve wildfire management and public health policies, including through a stronger engagement of the general population, and promote the implementation of more effective preventive and mitigation strategies to protect the health of affected communities during wildfire season.

Inhalation exposure to indoor air pollutants during moderate- and high-intensity physical exercise in commercial fitness microenvironments - Cátia Peixoto; Maria do Carmo Pereira; Simone Morais; Klara Slezakova (Building and Environment, 2025)

Occupational exposure to wildland firefighting and its effects on systemic DNA damage - Filipa Esteves; Joana Madureira; Carla Costa; Joana Pires; Bela Barros; Sara Alves; Josiana Vaz; Marta Oliveira; Klara Slezakova; Adília Fernandes; Maria do Carmo Pereira; Simone Morais; et al. (International Journal of Hygiene and Environmental Health, 2025)

Glyphosate and glyphosate-based herbicides induce Poecilia reticulata to maintain redox equilibrium during and after coexposure to iron oxide nanoparticles (y-Fe2O3) - João Marcos de Lima Faria; Mariana Morozesk; Iara da Costa Souza; Victória Costa da Silva; Luiz Arthur Mendes Bataus; Simone Maria Teixeira de Sabóia-Morais; Marisa Narciso Fernandes (Aquatic Toxicology, 2025)

Sex-related differences in eating behaviors during COVID-19 pandemic: A systematic review with metanalysis - Simone Gonzaga do Carmo; Maísa Miranda Araújo; Maria Eduarda Coelho Bittencourt Cavalcanti; Ana Claudia Morais Godoy Figueiredo; Kênia Mara Baiocchi de Carvalho; Patrícia Borges Botelho (Appetite, 2024)

Biomonitoring of firefighters' exposure to priority pollutant metal(loid)s during wildland fire combat missions: Impact on urinary levels and health risks - Ana Margarida Paiva; Bela Barros; Rui Azevedo; Marta Oliveira; Sara Alves; Filipa Esteves; Adília Fernandes; Josiana Vaz; Maria José Alves; Klara Slezakova; Maria do Carmo Pereira; João Paulo Teixeira; et al. (Science of The Total Environment, 2024)

Environmental contamination with polycyclic aromatic hydrocarbons and contribution from biomonitoring studies to the surveillance of global health - Joana Teixeira; Cristina Delerue-Matos; Simone Morais; Marta Oliveira (Environmental Science and Pollution Research, 2024)
This work presents an integrated overview of polycyclic aromatic hydrocarbons’ (PAHs) ubiquity comprising environmental contamination in the air, aquatic ecosystems, and soils; characterizes the contamination in biota; and identifies main biomonitors and human exposure to PAHs and associated health risks. Urban centers and industrial areas present increased concentrations in the air (1344.4–12,300 versus 0.03–0.60 ng/m 3 in industrial/urban and rural zones) and soils (0.14–1.77 × 10 6 versus 2.00–9.04 × 10 3 versus 1.59–5.87 × 10 3 ng/g in urban, forest, and rural soils), respectively. Increased concentrations were found in coastal zones and superficial waters as well as in sediments (7.00 × 10 4 –1.00 × 10 9 ng/g). Benzo(a)pyrene, a carcinogenic PAH, was found in all environmental media. Mosses, lichens, tree leaves, bivalves, cephalopods, terrestrials’ snails, and honeybees are good biomonitors of biota contamination. More studies are needed to improve characterization of PAHs’ levels, distribution, and bioaccumulation in the environmental media and assess the associated risks for biota and human health. Actions and strategies to mitigate and prevent the bioaccumulation of PAHs in the environment and trophic chains toward the WHO’s One-Health Perspective to promote the health of all ecosystems and human life are urgently needed.

Assessment of Portuguese fitness centers: Bridging the knowledge gap on harmful microbial contamination with focus on fungi - Carla Viegas; Cátia Peixoto; Bianca Gomes; Marta Dias; Renata Cervantes; Pedro Pena; Klara Slezakova; Maria do Carmo Pereira; Simone Morais; Elisabete Carolino; Magdalena Twarużek; Susana Viegas; et al. (Environmental Pollution, 2024)

Biomonitoring of polycyclic aromatic hydrocarbons exposure and short-time health effects in wildland firefighters during real-life fire events - Ana Margarida Paiva; Bela Barros; Marta Oliveira; Sara Alves; Filipa Esteves; Adília Fernandes; Josiana Vaz; Klára Slezáková; João Paulo Teixeira; Solange Costa; Simone Morais (Science of The Total Environment, 2024)

Assessing ecological risks and spatial distribution of potentially toxic elements in soils from anthropized environments in a watershed at the caatinga-Atlantic forest ecotone in Brazil - Kaíque Mesquita Cardoso; Clístenes Williams Araújo do Nascimento; Simone Aparecida da Silva Lins; Carol Chaves Nascimento; Raiane Lima Oliveira; Douglas Gonçalves da Silva; Pâmalla Graziely Carvalho Morais; Cácio Luiz Boechat (Environmental Research, 2024)

Gravimetric, morphological, and chemical characterization of fine and ultrafine particulate matter inside fire stations - Gabriel Sousa; Joana Teixeira; Rui Azevedo; Agostinho Almeida; Cristina Delerue-Matos; Simone Morais; Xianyu Wang; Francisca Rodrigues; Maria Freitas; Marta Oliveira (Building and Environment, 2024)

Chemical, ecotoxicological, cytotoxic, and mutagenic evaluation of gelling agents used in the production of 70% alcohol gel - Natália Cristina de Oliveira D’Alessandro; Ryan Marques Rezende; João Antonio Xavier Manso; Dayane Cristina da Costa; Simone Maria Teixeira de Saboia-Morais; Daniela de Melo e Silva; Emmanuel Bezerra D′Alessandro; Hugo Freire Nunes; Nelson Roberto Antoniosi Filho (Environmental Toxicology and Pharmacology, 2024)

Different starch sources result in distinct responses to diets digestibility, fecal microbiota and fermentative metabolites, and postprandial glycemic response in dogs - Gislaine Cristina Bill Kaelle; Taís Silvino Bastos; Renata Bacila Morais dos Santos de Souza; Eduarda Lorena Fernandes; Simone Gisele de Oliveira; Ananda Portella Félix (Animal Feed Science and Technology, 2023)

Watershed-scale assessment of environmental background values of soil potential toxic elements from the Caatinga and Atlantic forest ecotone in Brazil - Kaíque Mesquita Cardoso; Cácio Luiz Boechat; Clístenes Williams Araújo do Nascimento; Maria Eugenia Ortiz Escobar; Douglas Gonçalves da Silva; Simone Aparecida da Silva Lins; Raiane Lima Oliveira; Pâmalla Graziely Carvalho Morais (Chemosphere, 2023)

Environmental assessment of on-site source-separated wastewater treatment and reuse systems for resource recovery in a sustainable sanitation view - Hugo Henrique de Simone Souza; Priscila de Morais Lima; Diego Lima Medeiros; Jéssica Vieira; Fernando Jorge Corrêa Magalhães Filho; Paula Loureiro Paulo; Pere Fullana-i-Palmer; Marc Árpad Boncz (Science of The Total Environment, 2023)

Assessment of coarse, fine, and ultrafine particulate matter at different microenvironments of fire stations - Joana Teixeira; Gabriel Sousa; Simone Morais; Cristina Delerue-Matos; Marta Oliveira (Chemosphere, 2023)

Co-exposure of iron oxide nanoparticles with glyphosate herbicides in Poecilia reticulata: Fish liver damages is reversible during iron accumulation and elimination period - João Marcos de Lima-Faria; Victória Costa da Silva; Lee Chen Chen; Diego Stéfani Teodoro Martinez; Simone Maria Teixeira de Sabóia-Morais (Chemosphere, 2023)

Performance assessment of the MOF adsorbent MIL-101 for removal of gaseous benzene and toluene: kinetic column modeling and simulation studies of fixed-bed adsorption - Amir Hossein Khoshakhlagh; Zohreh Saadati; Farideh Golbabaei; Simone Morais; Ana Margarida Paiva; Seyed Jamaleddin Shahtaheri (Environmental Science and Pollution Research, 2023)

Musa spp. cultivars as a neutralising source against some toxic activities of Bothrops and Crotalus genus snake venoms - Márcia Matos da Silva; Gerso Pereira Alexandre; Marta Regina Magalhães; Ana Maria Torres; Lucilia Kato; Victória Costa da Silva; Simone Maria Teixeira de Saboia Morais; Armando Garcia Rodriguez; Taícia Pacheco Fill; Alana Kelyene Pereira; Jussara Roque; Jorge Luiz Souza Simão; et al. (Toxicon, 2023)

Ovaries of guppies (Poecilia reticulata) investigated in pre-embryonic, embryonic and post-embryonic stages after exposure to maghemite nanoparticles (y-Fe2O3) associated with Roundup® and glyphosate, followed by recovery period evaluation - Victória Costa da Silva; João Marcos de Lima-Faria; Lucas Nunes Guimarães; Matheus Santos Costa; Phâmella Neres de Lima; Karina Simões; Lázaro Wender Oliveira de Jesus; Simone Maria Teixeira de Sabóia-Morais (Environmental Toxicology and Pharmacology, 2023)

Embryotoxicity of silica nanoparticles in the drug delivery of domperidone in zebrafish - Lorranny Pereira de Assis Valadares; Larise Caroline Oliveira Lima; Simone Maria Teixeira de Saboia-Morais; Tatiane Moraes Arantes; Fernando Henrique Cristovan; Naiton Martins da Silva; Aline Borges Andrade; Sandra Aparecida Benite Ribeiro; Benner Geraldo Alves; Barbara do Carmo Rodrigues Virote; Ives Charlie da Silva; Mônica Rodrigues Ferreira Machado (Aquatic Toxicology, 2023)

In vitro propagation of Paepalanthus chiquitensis Herzog (Eriocaulaceae), an endangered everlasting flower species - Carollayne Gonçalves-Magalhães; Tâmara Prado de Morais; Denise Garcia de Santana; Simone Abreu Asmar; João Paulo Ribeiro-Oliveira; José Magno Queiroz Luz (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

ESG approach in the valorization of cocoa (Theobroma cacao) by-products by subcritical water: Application in the cosmetic industry - Jaroslava Švarc-Gajić; Tanja Brezo-Borjan; Valentin Dzedik; Francisca Rodrigues; Simone Morais; Cristina Delerue-Matos (Sustainable Chemistry and Pharmacy, 2023)

Lack of molecular evidence of fecal-borne viruses in capybaras from São Paulo state, Brazil, 2018–2020: a minor public health issue - Lais Sampaio de Azevedo; Yasmin França; Ellen Viana; Roberta Salzone Medeiros; Simone Guadagnucci Morillo; Raquel Guiducci; Cibele Daniel Ribeiro; Heloisa Rosa Vieira; Karolina Morales Barrio-Nuevo; Mariana Sequetin Cunha; Juliana Mariotti Guerra; Dulcilena de Matos Castro e Silva; et al. (Brazilian Journal of Microbiology, 2023)

Effects of dietary supplementation with a blend of functional oils to fecal microbiota, and inflammatory and oxidative responses, of dogs submitted to a periodontal surgical challenge - Renata Bacila Morais dos Santos de Souza; Nayara Mota Miranda Soares; Taís Silvino Bastos; Gislaine Cristina Bill Kaelle; Simone Gisele de Oliveira; Ananda Portella Félix (Animal Feed Science and Technology, 2023)

Treatment of cosmetic industry wastewater by flotation with Moringa oleifera Lam. and aluminum sulfate and toxicity assessment of the treated wastewater - Nathalia Santos Araújo; Nathália Ferreira Souza; João Marcos de Lima-Faria; Andressa Tuane Santana Paz; Paulo Sérgio Scalize; Simone Maria Teixeira de Sabóia-Morais; Humberto Carlos Ruggeri Junior; Edemilson Cardoso da Conceição (Environmental Science and Pollution Research, 2022)

Human astrovirus types 1, 4 and 5 circulating among children with acute gastroenteritis in a rural Brazilian state, 2010-2016 - Adriana Luchs; Kaelan Tardy; Roozbeh Tahmasebi; Simone Guadagnucci Morillo; Flavio Augusto de Pádua Milagres; Vanessa dos Santos Morais; Rafael Brustulin; Maria da Aparecida Rodrigues Teles; Lais Sampaio de Azevedo; Ellen Viana de Souza; Roberta Salzone Medeiros; Yasmin França Viana Pires de Souza; et al. (Archives of Virology, 2021)

Environmentally relevant concentrations of benzophenone-3 induce differential histopathological responses in gills and liver of freshwater fish - Sara dos Santos Almeida; Vinícius Silva Oliveira; Mariana Ribeiro Dantas; Leonardo Luiz Borges; Simone Maria Teixeira de Sabóia-Morais; Thiago Lopes Rocha; Elisa Flávia Luiz Cardoso Bailão (Environmental Science and Pollution Research, 2021)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Critical review of micro-extraction techniques used in the determination of polycyclic aromatic hydrocarbons in biological, environmental and food samples - B. K. K. K. Jinadasa; Fabrice Monteau; Simone Morais (Food Additives & Contaminants: Part A, 2020)

Exposure to polycyclic aromatic hydrocarbons and assessment of potential risks in preschool children - Marta Oliveira; Klara Slezakova; Cristina Delerue-Matos; Maria do Carmo Pereira; Simone Morais (Environmental Science and Pollution Research, 2015)

Levels and risks of particulate-bound PAHs in indoor air influenced by tobacco smoke: a field measurement - Klara Slezakova; Dionísia Castro; Cristina Delerue-Matos; Simone Morais; Maria do Carmo Pereira (Environmental Science and Pollution Research, 2014)

Trace metals in size-fractionated particulate matter in a Portuguese hospital: exposure risks assessment and comparisons with other countries - Klara Slezakova; Simone Morais; Maria do Carmo Pereira (Environmental Science and Pollution Research, 2014)

Mutagenicity and Genotoxicity in Gill Erythrocyte Cells of Poecilia reticulata Exposed to a Glyphosate Formulation - José De Souza Filho; Caio César Neves Sousa; Cláudio Carlos Da Silva; Simone Maria Teixeira De Sabóia-Morais; Cesar Koppe Grisolia (Bulletin of Environmental Contamination and Toxicology, 2013)

Antinociceptive and wound healing activities of Croton adamantinus Müll. Arg. essential oil - Rafael Matos Ximenes; Lenise de Morais Nogueira; Nathalia Maria Rodrigues Cassundé; Roberta Jeane Bezerra Jorge; Simone Maria dos Santos; Lucimere Paulino Machado Magalhães; Monalisa Ribeiro Silva; Glauce Socorro de Barros Viana; Renata Mendonça Araújo; Kêsia Xisto da Fonseca Ribeiro de Sena; Julianna Ferreira Cavalcanti de Albuquerque; René Duarte Martins (Journal of Natural Medicines, 2013)